20 years of common European monetary policy: Reasons to celebrate - Jan Philipp Fritsche; Patrick Christian Harms (DIW Weekly Report, 2019)
Twenty years after the introduction of the euro, this Weekly Report uses an empirical analysis to assess the performance of monetary policy in the EMU founding states. It is often claimed that the monetary policy of the European Central Bank (ECB) cannot outperform its national predecessors, as the euro area countries experience different business cycles yet share a common interest rate. However, the present analysis shows that the ECB's common monetary policy has been more adept at stabilizing the economy than most of its national predecessors from the perspective of the member states. With a common currency, European monetary policy has also become largely independent of exchange rates. However, the central bank is unable to counter long-term macroeconomic imbalances. To protect euro area countries from crises more effectively, priority should be given to reforming the monetary union and fiscal policy as well as to completing the Banking Union and the Capital Markets Union. Mistakes in crisis management must be openly discussed in order to address the temptation some have to renationalize economic and monetary policy; the ECB's monetary policy should not be a scapegoat.
Keywords: C32; E42; E52; F45; 330; Economic and Monetary Union; ECB; Euro Area; Structural Vector Autoregressions; Monetary Policy Stress; Sign Restrictions; Heteroskedasticity